TRANSVAGINAL ECHOCARDIOGRAPHY FOR THE PRENATAL DETECTION OF THE CONGENITAL HEART DISEASES - E.A. Shevchenko (Union of pediatricians of Russia, 2009)
The ultrasonic study in the early pregnancy may successfully be used to perform the early prenatal detection of the congenital heart diseases in fetuses with the non cardiac abnormalities and sonographic markers of the chromosome pathology.Key words: fetus, early pregnancy, congenital heart diseases, non cardiac abnormalities, transvaginal echocardiography.